Performance of the new CMS-HF Online Radiation Damage Monitoring System - Gonultas Berat; Onel Yasar; Gülmez Erhan (EPJ Web of Conferences)
The CMS-HF Calorimeter is designed to detect forward going particles. Discovery type events are believed to produce high energy particles going at forward angles. Hence, it is important to determine the particle energies accurately by making sure that the detectors have the right calibration all the time. The CMS-HF calorimeters have quartz fibers as the active element. Particle showers caused by the high energy particles travelling through the calorimeter produce the Cherenkov light in the quartz fibers. Particle energies are determined from the signals produced in the PMTs by the Cherenkov light reaching them. Damage in the fibers caused by the radiation during the collisions increases the attenuation in the fibers resulting in less light reaching the PMTs for the same energy. The HF online radiation monitoring system is designed to measure the attenuation of the light in the fibers independently and to provide the correction factors for the energy calibration as a function of the luminosity during the run period. The system was upgraded and commissioned at the end of the Run II. The correction factors for the 2022 run period were obtained both in terms of time and luminosity. The results were normalized to those at the lowest eta values so that the measurements could be compared with the values obtained from the collision data. The recovery effect in the fibers is also observed in the measurements done by the online system. The same measurements were done for the 2023 run period.